PEMBUATAN SET EKSPERIMEN UNTUK MENENTUKAN KOEFISIEN KINETIK DAN KOEFISIEN RESTITUSI - HARIS, VENNY; Lizelwati, Novia (IAIN Batusangkar, 2016)
This study aims to determine the design specifications set tool-making experiments to determine the kinetic coefficients and a coefficient of restitution of the collision of two objects using laser diode and sensor based LDR arduino uno. Results of the study is the design tool set of experiments could measure the kinetic coefficient between the glass material with glass with a relative error of 2.5%, wood with wood with a relative error of 1%, and steel materials with wood with a relative error of 0.5%. The coefficient of restitution is obtained for glass with glass material is 0.062, wood with wood is 0:49, and steel materials with wood is 0:22.Key words: kinestetic cooficient, restitution, sensor, laser dioda, LDR, arduino uno